2019
DOI: 10.3390/molecules24183288
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of a Modular System—Synthesis and Characterization of an s-Triazine-Based Carboxylic Acid Ester Bearing a Galactopyranosyl Moiety and an Enormous Boron Load

Abstract: The amount of boron accumulated in tumor tissue plays an important role regarding the success of the boron neutron capture therapy (BNCT). In this article, we report a modular system, combining readily available starting materials, like glycine, 1,3,5-triazine and the well-known 9-mercapto-1,7-dicarba-closo-dodecaborane(12), as well as α-d-galactopyranose for increased hydrophilicity, with a novel boron-rich tris-meta-carboranyl thiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Successful reproduction of the mentioned synthetic approach (Scheme 3, steps a to c) was already reported using a three carborane-bearing mercapto derivative as a nucleophile. 26 Attempts to prepare 12 or 5 directly in one-pot syntheses, using DIPEA as a base, failed and only produced the monosubstituted derivative tert-butyl-N-[4-chloro-6-(1,7-dicarbacloso-dodecaboran-9-ylthio)-1,3,5-triazin-2-yl]-N-(1′,2′:3′,4′-di-Oisopropylidene-6′-deoxy-α-D-galactopyranos-6′-yl)glycinate (SP1) in 15% yield or the side product N-ethyl-N-isopropyl-4,6-bis-(1,7-dicarba-closo-dodecaboran-9-ylthio)-1,3,5-triazine-2-amine (SP2) in 10% yield (details are given in the ESI †). Selective cleavage of the ester group of 12 (under maintenance of the isopropylidene protecting groups of the galactopyranosyl moiety) with trifluoroacetic acid in anhydrous toluene or dichloromethane gave the final product 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful reproduction of the mentioned synthetic approach (Scheme 3, steps a to c) was already reported using a three carborane-bearing mercapto derivative as a nucleophile. 26 Attempts to prepare 12 or 5 directly in one-pot syntheses, using DIPEA as a base, failed and only produced the monosubstituted derivative tert-butyl-N-[4-chloro-6-(1,7-dicarbacloso-dodecaboran-9-ylthio)-1,3,5-triazin-2-yl]-N-(1′,2′:3′,4′-di-Oisopropylidene-6′-deoxy-α-D-galactopyranos-6′-yl)glycinate (SP1) in 15% yield or the side product N-ethyl-N-isopropyl-4,6-bis-(1,7-dicarba-closo-dodecaboran-9-ylthio)-1,3,5-triazine-2-amine (SP2) in 10% yield (details are given in the ESI †). Selective cleavage of the ester group of 12 (under maintenance of the isopropylidene protecting groups of the galactopyranosyl moiety) with trifluoroacetic acid in anhydrous toluene or dichloromethane gave the final product 5.…”
Section: Resultsmentioning
confidence: 99%
“…10,12,[14][15][16][17]23 However, there are still some major challenges, including the selectivity of the chosen biomolecules for a specific type of tumour, the required high concentration of boron-10 in the cancer cell, the water solubility of the final bioconjugate, and the neutron beam quality, 24 which are also the focus of current research. 13,[17][18][19]25,26 Recently, we reported the synthesis of s-triazine-based boron-rich carboxylic acids. 27 Preliminary studies showed that the incorporation of more than one s-triazine-based bis(carboranyl) derivative into the breast tumour-selective peptide [F 7 ,P 34 ]-neuropeptide Y leads to a decrease or even total loss of the hY 1 receptor activation potency.…”
Section: Introductionmentioning
confidence: 99%
“…After an initial demonstration of the synthetic feasibility, two units of 9-mercaptometa-carborane and some simple nucleophiles (Scheme 8) were introduced on a triazine core [54]. More complex derivatives containing a galactose unit were obtained exploiting previously developed sugar-containing building blocks and 9-mercapto-meta-carborane 47 (Scheme 9) or a newly developed tris-cluster derivative 53 of 47 (Scheme 10) [55,56]. More complex derivatives containing a galactose unit were obtained exploiting previously developed sugar-containing building blocks and 9-mercapto-meta-carborane 47 (Scheme 9) or a newly developed tris-cluster derivative 53 of 47 (Scheme 10) [55,56].…”
Section: 14 X For Peer Review 11 Of 19mentioning
confidence: 99%
“…More complex derivatives containing a galactose unit were obtained exploiting previously developed sugar-containing building blocks and 9-mercapto-meta-carborane 47 (Scheme 9) or a newly developed tris-cluster derivative 53 of 47 (Scheme 10) [55,56]. Compound 47 was also used as a scaffold and decorated with two galactosyl moieties and a carboxymethyl group which allowed the conjugation with neuropeptide Y (NPY), known to be recognized by tumor-overexpressed G protein-coupled receptor (GPCR) [57].…”
Section: 14 X For Peer Review 11 Of 19mentioning
confidence: 99%
“…Here, we report the development of small molecules representing potential boron-rich coupling partners for tumor-selective molecules based on a modular strategy [ 47 , 48 , 49 ] combining readily available starting materials, like meta -carborane, α- d -galactopyranose and glycine or ethylenediamine derivatives (compounds 5 and 6 in Scheme 1 ). Compounds bearing a primary amine or carboxylic acid group represent potentially universal coupling partners for biomolecules [ 48 ]; representative coupling experiments are also included here to demonstrate the generalizability of this approach.…”
Section: Introductionmentioning
confidence: 99%